OPTIMALISASI KEGIATAN JUMAT IBADAH UNTUK MENINGKATKAN KARAKTER RELIGIUS DI SEKOLAH: PROGRAM PENGABDIAN MAHASISWA KKN - Abdullatif, Ahmad; Ramadhan, Syaiful; Karadona, Rosika Indri; Rahma, Rahma; Hasan, Nur; Masnah, Masnah; Azis, Andi Mattotoran (Universitas Negeri Makassar, 2025)
The Friday Worship Activities Optimization Program to Improve Religious Character in Schools aims to increase religious awareness and shape the character of students through a more systematic and interactive approach. This research uses the Participatory Action Research (PAR) method, which involves Real Work Lecture (KKN) students, teachers and students in the process of planning, implementing, evaluating and developing the Friday Worship program. Activities carried out include congregational dhuha prayers, dhikr, murajaah memorizing surahs, religious lectures, and daily prayers. The results of the program show an increase in student interest and participation in worship activities, a deeper understanding of religious values, as well as positive changes in attitudes in daily life. Support from schools, teachers and the community plays an important role in the success of this program. Apart from that, this program provides valuable experience for KKN students in applying the knowledge they gain at university into real practice in society. The conclusion of this research is that optimizing Friday Worship activities can be an effective means of forming students' religious character in a sustainable manner. With an approach that involves all elements of the school, this activity not only becomes routine, but also forms a religious culture in the school environment. It is hoped that this program can continue to be implemented and developed as part of a religious-based character education strategy in schools.